Contribution and value of biomarkers in acute aortic syndromes - Yildiz, Mustafa; Behnes, Michael; Akın, Ibrahim (Current pharmaceutical biotechnology, 2017)
Background: Acute aortic syndromes, being mostly underdiagnosed due to unspecific symptoms, are associated with high morbidity and mortality. Diagnosis carried out by transesophageal echocardiography, computed tomography and magnetic resonance imaging. However, there are lots of biochemical assays being investigated, but none of them used reliably to identify acute aortic syndromes. Biomarkers could accelerate the diagnostic time with cost effective way and could get place in definitive diagnostic algorithm of acute aortic syndrome. This review aims to identify contribution and value of biomarkers in acute aortic syndromes. Methods: We searched the contribution and value of biomarkers such as D - Dimer, Smooth muscle myosin heavy chain (sm - MHC), Calponin, and Soluble elastin fragments (sELAF) in acute aortic syndromes at the literature. Results: Twenty two actual papers were included in this review for searching the contribution and value of biomarkers in the acute aortic syndromes. Conclusion: Biomarkers accelerate the diagnosis and direct patients to imaging modalities with a risk classification. Plenty of biomarkers have been investigated so far but none of them were used in clinical routine. Currently none of the biomarkers can reliably identify acute aortic syndromes. Each of them has some limitation in term of sensitivity or specificity. Although, there is no single biomarker that can be safely used but a combination of the assays may increase the sensitivities and specificities.